Entrepreneurial innovation: The sustainable ventures of Human Development Credit beneficiaries - Granizo, Ximena; Delgado, Carlos (Heritage and Sustainable Development, 2024)
This research article is developed in the socioeconomic context of the province of Chimborazo where the beneficiaries of the Associative Human Development Credit (HDC) present entrepreneurial intentions. The methodology used presents a quantitative research design of an explanatory type, with a causal and cross-sectional approach since it aims to measure the degree of a causal relationship between the indicators that influence the construction of entrepreneurial behavior and the entrepreneurial intention that arises in people who receive the HDC in the province of Chimborazo; a questionnaire was applied to a sample of 260 beneficiaries and subsequently, a structural equation model was implemented with the theory of planned action (TPA). The findings support each hypothesis, demonstrating their relevance and validity in the context of the study. Personal attitude emerges as a determining factor, with a considerably high t-statistic (4.563) and a p-value of 0.000, indicating a robust and significant relationship with entrepreneurial intention. Perceived control also shows a significant influence on entrepreneurial intention with a t-statistic of 2.157 and a p-value of 0.015. In contrast, social norms do not seem to have a significant impact, as indicated by the low t-statistic (0.401) and a p-value of 0.641. This result points to the fact that beliefs about social approval are not determinant in the decision to undertake in this specific context of sustainable ventures. It is concluded that the TPA structural equation model is suitable for predicting the factors influencing entrepreneurial intention.